PENGARUH LINGKUNGAN KERJA, PENGALAMAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN CV. DIAN MANDIRI - Gde Bayu Surya Parwita; Made Ika Prastyadewi; Ida Ayu Nyoman Tri Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Employee performance is one of the important factors because the progress of an organization or company is very dependent on its human resources. This study aims to how much influence the work environment, work experience and compensation on employee performance at CV. Dian Mandiri. The population in this study were 51 employees of CV. Dian Mandiri. The sample used is the saturated sample method with 51 respondents. Data collection methods are observation, interviews and questionnaires. The analysis technique used in this research multiple regression analysis. The results of this study indicate that the work environment, work experience and compensation have a positive and significant effect on employee performance, the leadership should create a comfortable work environment for employees, provide job training to employees and provide appropriate benefits to employees, so as to improve employee performance at CV. Dian Mandiri.